Management Perspectives Pertaining to Root Cause Analyses of Nunn-McCurdy Breaches, Volume 4 Program Manager Tenure, Oversight of Acquisition Category II Programs, and Framing Assumptions - Arena, Mark V. (RAND Corporation, 2013)
The authors investigate whether the tenure of program managers contributes to Nunn-McCurdy breaches. They also examine the existing decentralized systems used to track cost growth to determine whether additional guidance and control are needed to make acquisition category II programs' performance more transparent. Finally, they investigate whether key assumptions, so-called framing assumptions, could be useful risk management tools.